Research on Vocational Education in Indonesia: A Bibliometric Analysis - Ronal Watrianthos; Ambiyar Ambiyar; Fahmi Rizal; Nizwardi Jalinus; Waskito Waskito (Universitas Negeri Padang, 2022)
Indonesia's education system separates vocational education from academic education. Vocational education, which was previously not a key focus for prospective students, should now be on par with academic education at both the secondary and higher education levels. However, research on Vocational Education in Indonesia is still limited, particularly articles in reliable indexed databases; therefore, research on Vocational Education in Indonesia is still readily available. This research aims to map studies in bibliometrics connected to research trends in Vocational Education in Indonesia. This study does a statistical analysis of the number of publications on